GOOD AND CORRECT USE OF INDONESIAN LANGUAGE IN GENERAL POSTERS FOR RI INDEPENDENCE - Yuni Ertinawati; Alya Hijria; Nurjihan Tiyoga, Rifaa Nazlaa (Media Inovasi Pendidikan dan Publikasi, 2024)
This research analyzes the good and correct use of Indonesian on public posters celebrating the 79th anniversary of the Republic of Indonesia. The aim is to find out how to use Indonesian properly and correctly on public posters, especially commemorating the 79th Independence Day of the Republic of Indonesia. The research method we use is analyzing a post on social media. The conclusion we have reached is that most young Indonesians do not use good and correct Indonesian when uploading things on social media.